Aneuploidy: Marker of Malignant Colorectal Adenomas - Stoian Marilena (Advanced Concepts in Pharmaceutical Research Vol. 7, 2024)
Abnormal DNA amounts are mostly caused by changes in the number of chromosomes and chromosomal deletions. The aim of this study is to further investigate if DNA aneuploidy can serve as an early marker of malignant transformation of colorectal adenomatous polyps. The study was performed on 50 colorectal polyps obtained through endoscopic polypectomy from 46 patients, aged 30 to 80, with a mean age of 60. One interesting observation in our study refers to the DNA index in polyps with focal carcinomatous lesions, in which the carcinomatous areas have similar DNA indexes to those from the strictly adenomatous regions of the polyp. The significant association between DNA aneuploidy and the size of the polyps is vital, as size is considered one of the most important predictors of carcinomatous transformation in an adenoma, followed in predictive ability by histopathological type and degree of dysplasia.